2019
DOI: 10.1186/s12872-018-0984-0
|View full text |Cite
|
Sign up to set email alerts
|

Modes of death and clinical outcomes in adult patients with hypertrophic cardiomyopathy in Thailand

Abstract: BackgroundThere are limited data about modes of death and major adverse cardiovascular events (MACEs) in patients with hypertrophic cardiomyopathy (HCM) in South East Asian population. The aim of the study was to examine modes of death and clinical outcomes in Thai patients with HCM.MethodsBetween January 1, 2009 and December 31, 2013, 166 consecutive patients with HCM diagnosed in our institution were evaluated. Five patients were excluded because of non-Thai ethnic groups (n = 3) and diagnosis of myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 42 publications
3
19
3
Order By: Relevance
“…Considering that the half-life of circulating cfDNA is rather short (15–20 min [ 52 ]) its source must be continuous as otherwise such a time window would be too short for its clinical detection. This is in line with the fact that NETs were reported to persist in the vasculature for days [ 53 , 54 , 55 , 56 ], and our preliminary data indicate that this is in fact significantly longer (Santocki and Kolaczkowska, unpublished). Thus, NETs can act as a continuous source of cfDNA and other NET components for over a prolonged period of time.…”
Section: On How Nets Cause Bystander Damagesupporting
confidence: 87%
“…Considering that the half-life of circulating cfDNA is rather short (15–20 min [ 52 ]) its source must be continuous as otherwise such a time window would be too short for its clinical detection. This is in line with the fact that NETs were reported to persist in the vasculature for days [ 53 , 54 , 55 , 56 ], and our preliminary data indicate that this is in fact significantly longer (Santocki and Kolaczkowska, unpublished). Thus, NETs can act as a continuous source of cfDNA and other NET components for over a prolonged period of time.…”
Section: On How Nets Cause Bystander Damagesupporting
confidence: 87%
“…Results from observational studies have consistently reported positive associations between dietary animal protein intake and risk of type 2 diabetes [ 5 ], coronary heart disease [ 6 , 7 ] and ischemic heart disease [ 8 ] and CVD-specific mortality [ 9 , 10 , 11 ], and inverse associations between dietary plant protein intake and cardiometabolic disorder outcomes [ 5 , 8 , 9 , 10 ]. Although potential mechanisms underpinning these associations have been attributed to the effects of animal or plant protein intake on traditional cardiometabolic risk factors (CMRFs), including lipid and lipoprotein profiles, glucose homeostasis biomarkers and low-grade chronic inflammation, and emerging risk factor serum uric acid or hyperuricemia [ 12 ], data supporting these assumptions are strikingly limited and inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Fifty-two single nucleotide polymorphisms (SNP) included in the present study from the genes ACE , ACE2 , AGT , AGTR1 , AGTR2 , MME , CMA1 , MAS1 , HIF1A , VEGFA , KDR , PGF and FLT1 ( Table S1 ) were selected from search in genomic public databases, in silico analysis and review of scientific literature, to identify putatively functional polymorphisms [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Polymorphisms with minor allele frequency below 1% were excluded [ 37 ].…”
Section: Methodsmentioning
confidence: 99%